Mempertahankan Kehidupan Dalam Koma: Telaah Dari Sisi Etika Kristani Pada Kasus Koma Vegetatif - Adiatmo, Kumoro; Simon, Simon; Harianto, Yusup Heri (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
In the age of significant medical technology advancements, the management of complex medical conditions such as vegetative states presents profound ethical dilemmas for families, healthcare providers, and the community. This study explores the role of Christian theology in guiding ethical decision-making amidst these challenges, focusing on the concept of